Analisis Jalur Faktor Makroekonomi Terhadap Return Saham Syariah - Ardina Talitha Nidya (Dept. Ekonomi Syariah FEB Universitas Airlangga, 2018)
This research aims to determine the influence of macroeconomic factors on the profitability and stock return of PT. Bank Panin Dubai Syariah, Tbk period 2014-2017. The approach is a quantitative approach using path analysis. The exogenous variables that used are inflation, Gross Domestic Product (GDP), BI rate, and exchange rate while the endogenous variable is stock return and the intervening variable is profitability. The result of this research indicates that inflation has no significant effect on profitability, GDP has no significant effect on profitability, BI rate influences positively significant on profitability, exchange rate influences negatively significant on profitability, inflation has no significant effect on stock return, GDP has no significant effect on stock return, BI rate has no significant effect on stock return, exchange rate influences negatively significant on stock return, and profitability has no significant effect on stock return of PT. Bank Panin Dubai Syariah, Tbk period 2014-2017